2021
DOI: 10.1002/minf.202100028
|View full text |Cite
|
Sign up to set email alerts
|

In silico Studies on the Interaction between Mpro and PLpro From SARS‐CoV‐2 and Ebselen, its Metabolites and Derivatives

Abstract: The COVID‐19 pandemic caused by the SARS‐CoV‐2 has mobilized scientific attention in search of a treatment. The cysteine‐proteases, main protease (Mpro) and papain‐like protease (PLpro) are important targets for antiviral drugs. In this work, we simulate the interactions between the Mpro and PLpro with Ebselen, its metabolites and derivatives with the aim of finding molecules that can potentially inhibit these enzymes. The docking data demonstrate that there are two main interactions between the thiol (−SH) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 112 publications
(126 reference statements)
3
41
0
Order By: Relevance
“…Ebselen has been proven to be a potent inhibitor of SARS-CoV-2 Mpro through HTS studies [48,49]. Not only in silico studies [50,51] but also in crystallographic studies [52] it has been shown that ebselen can bind to the relevant region of the Mpro. Accordingly, studies on the effect of ebselen on Mpro crystals support the precipitation we observed in our Mpro-ebselen sample, and hence the potential inhibitor effect of ebselen on SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen has been proven to be a potent inhibitor of SARS-CoV-2 Mpro through HTS studies [48,49]. Not only in silico studies [50,51] but also in crystallographic studies [52] it has been shown that ebselen can bind to the relevant region of the Mpro. Accordingly, studies on the effect of ebselen on Mpro crystals support the precipitation we observed in our Mpro-ebselen sample, and hence the potential inhibitor effect of ebselen on SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, worldwide laboratories share a massive amount of genomic information, which is most difficult to analyze without bioinformatics tools. Additionally, project many potential drugs and natural products against SARS-CoV-2 with the CADD platform [ 18 , 79 , 98 , 99 , 100 ]. At present, several tools and databases of bioinformatics are available for gene analysis to vaccine/drug development.…”
Section: Resultsmentioning
confidence: 99%
“…From SAR analysis, cyclodecene (C 10 H 18 ), cyclohexene oxide (C 6 H 10 O), and γ-butyrolactone or dihydrofuran-2(3H)-one (C 4 H 6 O 2 ) with chlorine in each in all three structures. Indeed, the presence of two methyl butyrate, one methyl acetate with a methyl−like group attachment project many potential drugs and natural products against SARS-CoV-2 with the CADD platform [18,79,[98][99][100]. At present, several tools and databases of bioinformatics are available for gene analysis to vaccine/drug development.…”
Section: Overall Drug Likeness and Sar Analysesmentioning
confidence: 99%
“…The mechanisms of these nucleophilic substitutions have been tackled in detail by several authors [25,[75][76][77][78]. Among the examples reported in literature, it is worth to mention the antidepressant lithium-like potential of ebselen as inositol monophosphatase inhibitor [79,80], as disruptor of protein Zn fingers [81,82], and, more recently, ebselen has been repurposed as SARS Cov 2 M pro inhibitor [83][84][85][86], justifying its antiviral activity measured in vitro.…”
Section: The Reduction Of Hydroperoxides By Gpx Mimics: the Case Of Ebselenmentioning
confidence: 99%